Fish faunas from the Late Jurassic (Tithonian) Vaca Muerta Formation of Argentina: One of the most important Jurassic marine ichthyofaunas of Gondwana - Gouiric Cavalli, Soledad (2015)
The marine deposits of the Vaca Muerta Formation (Tithonian-Berriasian) houses one of the most diverse Late Jurassic ichthyofaunas of Gondwana. However, most of the specimens remain undescribed. Jurassic fishes have been recovered from several localities at Neuquén Province (i.e., Picún Leufú, Plaza Huincul, Cerro Lotena, Portada Las Lajas, Los Catutos, and Arroyo Covunco) but also from Mendoza Province (i.e., La Valenciana, Los Molles, and Arroyo del Cajón Grande). Presently, the fish fauna of Los Catutos, near Zapala city (Neuquén Province), has yielded the highest number of specimens, which are taxonomically and morphologically diverse. At Los Catutos locality, the Vaca Muerta Formation is represented by the Los Catutos Member, which is considered the only lithographic limestones known in the Southern Hemisphere. Here, we review the Tithonian fish faunas from the Vaca Muerta Formation. During Late Jurassic times, the actual Argentinian territory could have been a morphological diversification center, at least for some actinopterygian groups. The apparently lower species diversity recorded in marine Jurassic ichthyofaunas of Argentina (and some Gondwanan countries) in comparison with Chilean and European fish faunas could be related to the fish paleontological research history in Gondwana and the low number of detailed studies of most of specimens recorded.